A Critique on the Book Myths of Ancient Bactria and Margiana on its Seals and Amulets - Hassan Basafa; Mohammadsadegh Davari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book Myths of Ancient Bactria and Margiana on its Seals and Amulets is basically a catalog of seals and amulets of BMAC culture, which was obtained during illegal excavations and was auctioned in the antique market of Afghanistan and Turkmenistan. All of these works have been documented by the author of the book, Sarianidi, one of the leading Russian archaeologists, and presented in English, along with a long article. The above work is one of the first publications of BMAC and since it was published in 1989, its study approach has been related to that time and also limited to the results and study hypotheses of the time of its compilation. Many of his hypotheses, especially about the origins of the people of this culture, and many others, need to be fundamentally reconsidered in light of recent research and findings. Since the above book is related to myths, in the present study, an attempt is made to critique and study it with an iconic approach and to explain and complete its study principles. The results indicate many strengths in terms of logical order of content, innovation and use of up-to-date sources compared to the time of compilation, as well as weaknesses in the archaeological foundations of Iran and in addition, strong weaknesses in specialized translation and editing.